THE EFFECT OF TOTAL QUALITY MANAGEMENT (TQM) ELEMENTS IMPLEMENTATION ON EMPLOYEE PERFORMANCE AT PT POMI PAITON - Yunita Primasanti; Noor Nailie Azzat; Bekti Yunanto; Christian Bionley Santoso (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Total Quality Management (TQM) is one of the tools used by business people in improving the progress of a company. The company uses Total Quality Management (TQM) because it has proven to be a big concern for managers in improving company performance. This study aims to determine the effect of Total Quality Management (TQM) on Employee Performance at PT POMI Paiton through three Total Quality Management (TQM) elements, namely teamwork; education and training; and employee engagement and empowerment. This type of research is quantitative with the research method used is associative. The source of this research data is an employee of PT POMI Paiton with a total sample of 86 respondents. Furthermore, the data collection method used is a questionnaire. Then, data processing techniques, namely validity and reliability tests, and data analysis techniques, namely multiple regression and hypothesis testing. The results of this study show that: 1) Simultaneously, the Total Quality Management (TQM) elements, namely teamwork; education and training; and employee involvement and empowerment affect employee performance at PT POMI Paiton. 2) Partially, the teamwork variable, education and training variable, have no positive and significant effect on employee performance; while employee engagement and empowerment variable have a positive and significant effect on employee performance. The regression results that have been carried out show the value of the coefficient of determination (R2) of 41.8%. This indicates that the large percentage of the three elements of the eleven elements of the Total Quality Management (TQM) can explain employee performance, while 58.2% is explained by other variables. The results of this study can provide information or as a signal to the company in improving the performance of company employees.